Gyrokinetic Stability Analysis of JET Pedestal Top Plasmas with Small-ELMs. Issue 1 (1st December 2022) - Dicorato, M.; Muraglia, M.; Camenen, Y.; Garcia, J.; Garbet, X.; Frigione, D.; Garzotti, L.; Lomas, P.; Rimini, F.; Sozzi, C.; Van Eester, D.
Abstract: In recent years, a strong effort has been dedicated to the development of tokamak plasma regimes alternative to the standard high confinement mode (H-mode) with type-I edge localized mode (ELM), i.e. ELM-free and small-ELM regimes, given the associated hardly sustainable energy and particle fluxes on plasma facing components. In this work, we will focus on new H-mode regimes with small-ELMs, the so-called baseline small-ELMs (BSE), characterized by high thermal confinement and low core impurity accumulation, which have been recently found at JET. In order to characterize the micro-turbulence at play at the top of the pedestal, an extensive local linear gyrokinetic analysis with the GKW code has been carried out. In particular, a comparison between a reference type-I ELM (#97395) and two BSE plasmas (#96994 and #94442) has been performed. The ion-scale (0.1 ≤ k θ ρ i ≤ 2) micro-turbulence is found to have different characteristics in the two regimes. Indeed, kinetic-ballooning modes (KBM) are destabilized in the type-I ELM regime at k θ ρ i ∼ 0.1, while they are stable in BSE regimes. In addition, negative (i.e. electron-diamagnetic-direction) frequency modes, identified as electron-temperature-gradient (ETG) modes, are destabilized at k θ ρ i ∼ 1.5 in the type-I ELM regime while BSE regimes are characterized by positive (i.e. ion-diamagnetic-direction) frequency modes. Meanwhile, at electron-scale (10 ≤ k θ ρ i ≤ 700) ETG modes are the dominant micro-instabilities in both regimes. Then, since BSE regimes are characterized by a higher impurity concentration at the pedestal, particular attention has been given to the role played by them. We found that impurities represent a critical player in the linear dynamics, strongly affecting the nature of micro-instabilities at ion-scale.